PENGARUH STRUKTUR KEPEMILIKAN, KINERJA, DAN RISIKO TERHADAP KOMPENSASI EKSEKUTIF - Rr Diana Atika Ghozali; Fuad Fuad (Diponegoro Journal of Accounting, 2015)
This study aimed to obtain empirical evidence about the influence of ownerhip structure, risk, and performance to the executive compensation. The population of this study was all banking industries are listed in Indonesia Stock Exchange (ISX) in 2011-2013. Sample of this study selected by used purposive sampling method. There are 35 banking industries each year which fulfilled criterion as the research sample. Data analysis was perform by used statistic program, Smart-PLS version 3.0. The result of this study showed that ownership structure had no significantly influence to the executive compensation of banking industries in Indonesia. Meanwhile, the performance and the risk significantly influence to the executive compensation of banking industries in Indonesia.